2013
DOI: 10.1209/0295-5075/104/47005
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic decoherence and Rabi oscillation damping of Mn2+and Co2+electron spin qubits in bulk ZnO

Abstract: We demonstrate by pulse EPR that two electron spin qubits in bulk ZnO, the Mn 2+ and the Co 2+ spin qubits, which have respectively long (T2 (6K) = 178 µs) and short (T2 (1.7K) = 9 µs) transverse spin coherence time T2 at low temperature, have however very short and similar Rabi oscillation damping times, on the order of TR ≈ 250 ns at low temperature. A detailed study of Mn 2+ spin qubits has shown that the main contribution to the Rabi oscilation damping rate is temperature independent and proportional to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The general design proposed here for quantum information processing could be applied, in principle, to all kind of electron spin qubits like phosphorous donors in silicon, 8,34 nitrogen donors or NV centers in diamonds, 3,4,9 transition metals ions or shallow donors in Zinc Oxide, 13,[25][26][27][28] N@C60 molecules, 29 paramagnetic defects in graphene, 33 paramagnetic dangling bonds arrays on hydrogen passivated silicon surface, 31 or supramolecular assemblies of paramagnetic molecules such as neutral radical molecules 30 or copper phtalocyanine molecules, 32 as long as regular dense arrays of them could be produced at precise positions nearby a ferromagnetic nanostripe. Without loss of generality and to be more quantitative, I focus here on a nanodevice made with silicon carbide and permalloy materials and build with top-down methods.…”
Section: Design and Fabrication Of A Nanodevice With Electron Spin Ar...mentioning
confidence: 99%
“…The general design proposed here for quantum information processing could be applied, in principle, to all kind of electron spin qubits like phosphorous donors in silicon, 8,34 nitrogen donors or NV centers in diamonds, 3,4,9 transition metals ions or shallow donors in Zinc Oxide, 13,[25][26][27][28] N@C60 molecules, 29 paramagnetic defects in graphene, 33 paramagnetic dangling bonds arrays on hydrogen passivated silicon surface, 31 or supramolecular assemblies of paramagnetic molecules such as neutral radical molecules 30 or copper phtalocyanine molecules, 32 as long as regular dense arrays of them could be produced at precise positions nearby a ferromagnetic nanostripe. Without loss of generality and to be more quantitative, I focus here on a nanodevice made with silicon carbide and permalloy materials and build with top-down methods.…”
Section: Design and Fabrication Of A Nanodevice With Electron Spin Ar...mentioning
confidence: 99%
“…We observe that the fast damping of the quantum oscillations is highly nonmonoexponential (see Supplemental Material, S3 [22]), likely due to an inhomogeneous B 1 across the sample. This can also be ascribed to a distribution of Mn electron spin coupling parameters due to strains caused by the proximity of the Mn 2+ ions to the QD surface [29,30] as well as to changes of the dipolar couplings occurring over the long nutation pulse [31]. The Fourier transform of the data recorded at different microwave powers (P mw ∝ B 2 1 ) show that the nutation frequency peaks shift from R /2π ∼ 8 MHz to 50 MHz with increasing B 1 [Fig.…”
Section: Rabi Oscillationsmentioning
confidence: 99%
“…The two parameters D and E stand for uniaxial and planar anisotropies, respectively. The effect of ZFS on the dynamic phase of isolated transition metals Co 2+ (S = 3/2), Mn 2+ (S = 5/2), Fe 3+ (S = 5/2), embedded in a zinc oxide (ZnO) single crystal is well established and it has been recently studied by EPR spectroscopy [20,21] where the parameters E and D are given. It has been shown that the magnetic anisotropy (ZFS) is maximum when the applied magnetic field B(t) is parallel to the unique axis c of ZnO, and zero, in the first-order approximation, for cos 2 (θ MA ) = 1/3 (see fig.…”
mentioning
confidence: 99%
“…The conventional Zeeman Berry's phase has been observed as energy shift in nuclear quadrupole resonance and analogue expressions are obtained [6]. This contribution vanishes only when the angle between the magnetization axis and the external magnetic field is zero [20,21], with simulation (continuous lines) according to eq. ( 7) [25].…”
mentioning
confidence: 99%